Apoptosis of mesenchymal stem cells is regulated by Rspo1 via the Wnt/β-catenin signaling pathway. Issue 1 (March 2019) - Cheng, Xiao-Xia; Yang, Qiao-Yan; Qi, Yong-Li; Liu, Zhi-Zhen; Liu, Dan; He, Sheng; Yang, Li-Hong; Xie, Jun
Abstract: Objective: The aim of this study was to investigate the effect and possible mechanism of action of roof plate-specific spondin1 (Rspo1) in the apoptosis of rat bone marrow mesenchymal stem cells (BMSCs). Methods: Osteogenic and adipogenic differentiation of BMSCs was identified by Alizarin Red and Oil Red O staining, respectively. BMSC surface markers (cluster of differentiation 29 [CD29], CD90, and CD45) were detected using flow cytometry. BMSCs were transfected with an adenoviral vector encoding Rspo1 (BMSCs-Rspo1 group). The expression levels of Rspo1 gene and Rspo1 protein in the BMSCs-Rspo1 group and the two control groups (untransfected BMSCs group and BMSCs-green fluorescent protein [GFP] group) were analyzed and compared by quantitative polymerase chain reaction and Western blot. The occurrence of apoptosis in the three groups was detected by flow cytometry and acridine orange-ethidium bromide (AO-EB) double dyeing. The activity of the Wnt/β-catenin signaling pathway was evaluated by measuring the expression levels of the key proteins of the pathway (β-catenin, c-Jun N-terminal kinase [JNK], and phospho-JNK). Results: Osteogenic and adipogenic differentiation was confirmed in cultured BMSCs by the positive expression of CD29 and CD90 and the negative expression of CD45. Significantly increased expression levels of Rspo1 protein in the BMSCs-Rspo1 group compared to those in the BMSCs (0.60 ± 0.05 vs . 0.13 ± 0.02; t =95.007, P =0.001) and BMSCs-GFP groups (0.60 ± 0.05 vs . 0.10 ± 0.02; t =104.842, P =0.001) were observed. The apoptotic rate was significantly lower in the BMSCs-Rspo1 group compared with those in the BMSCs group ([24.06 ± 2.37]% vs . [40.87 ± 2.82]%; t = 49.872, P = 0.002) and the BMSCs-GFP group ([24.06 ± 2.37]% vs . [42.34 ± 0.26]%; t = 62.358, P = 0.001). In addition, compared to the BMSCs group, the protein expression levels of β-catenin (2.67 ± 0.19 vs . 1.14 ± 0.14; t = −9.217, P = 0.000) and JNK (1.87 ± 0.17 vs . 0.61 ± 0.07; t = −22.289, P = 0.000) were increased in the BMSCs-Rspo1 group. Compared to the BMSCs-GFP group, the protein expression levels of β-catenin (2.67 ± 0.19 vs . 1.44 ± 0.14; t = −5.692, P = 0.000) and JNK (1.87 ± 0.17 vs . 0.53 ± 0.06; t = −10.589, P = 0.000) were also upregulated in the BMSCs-Rspo1 group. Moreover, the protein expression levels of phospho-JNK were increased in the BMSCs-Rspo1 group compared to those in the BMSCs group (1.89 ± 0.10 vs . 0.63 ± 0.09; t = −8.975, P = 0.001) and the BMSCs-GFP group (1.89 ± 0.10 vs . 0.69 ± 0.08; t = −9.483, P = 0.001). Conclusion: The Wnt/β-catenin pathway could play a vital role in the Rspo1-mediated inhibition of apoptosis in BMSCs.